Thread gauge calibration for industrial applications - Primožič Merkač, Tadeja (Strojniški vestnik, 2010)
There are two most commonly used methods for calibration of thread rings, with different measuring uncertainty. The method of mechanical sensing with two balls is mostly used on one-axial measuring machines and on coordinate measuring machines. However, the method of calculating the core diameter of the thread ring combined with the technique of adaptation (in accordance with the method of the smallest squares) is used on the profile scanner. The required tolerances, which are very narrow for adjustable and laboratory thread ring, so the measuring uncertainty may be too high when using the method of mechanical sensing with two balls, and the low quality of some control rings, are the decisive factors for choosing an appropriate method in the industry. This also depends on the laboratoryćs capability of executing a specific method. The measurements of the core diameter of thread rings, which are the main topic of this article, were included into an international inter-comparison in which the main subject was the same thread ring as the one mentioned in this article.
Keywords: kalibracija; merilna negotovost; navoj; navojni obroč